The impact of mining exploitation on community interaction: A social and environmental perspective - Rahmawati, Citra Tri; Alhaqi, Riandika Abdul Hafizh (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: Nickel mining activities on Gebe Island in Halmahera Tengah, Maluku Utara, contribute to the national economy by boosting regional income, employment, and infrastructure development. However, the lack of human resources to manage natural resources has led to significant environmental degradation and socio-economic challenges, particularly post-mining. This study analyzes the environmental and socio-economic impacts of nickel mining on the island. Method: A qualitative research approach was used to assess the current conditions of Gebe Island's environment and socio-economic landscape. The study focused on two key variables: human interaction and environmental interaction, analyzing their relationship and impacts. Findings: The study identified several negative environmental impacts from nickel mining, including landscape alterations, loss of fertile soil, increased critical land, reduced water quality (surface and marine), diminished populations of endemic plants, and disruptions to mangrove and coral reef ecosystems. Additionally, there is a decline in socio-economic life in the post-mining phase, impacting community well-being. Conclusion: To mitigate these impacts, the government must involve the community in the management and rehabilitation of the mining areas. Empowering local populations and increasing stakeholder cooperation are critical for ensuring the sustainable application of environmental laws and improving post-mining socio-economic conditions. Novelty/Originality of this Study: This research offers a detailed examination of the socio-economic and environmental consequences of nickel mining on Gebe Island. It provides a unique perspective on the need for community involvement and local empowerment to address mining-related challenges and enhance environmental sustainability.